A Bibliometric Analysis Ethical Perspectives on SDGs Based Education Goals Using VOSViewer - Sumadisastro, Witzir; Robandi, Babang; Fahrizal, Diki (PEDAGOGIA, 2024)
This study investigates the integration of ethical perspectives into the frameworks of Education for Sustainable Development (ESD) and Society 5.0, with a focus on their alignment with the Sustainable Development Goals (SDGs). Utilizing a bibliometric analysis, the research examines academic and professional literature published between 2010 and 2024. Data was collected from Google Scholar using keywords such as "Ethical Education," "Sustainable Development Goals and Education," and "Technology in Education." The analysis employed VOSviewer to map and visualize thematic connections and subject linkages within the literature.The findings indicate a notable increase in research on ethical education and the SDGs, with publication peaks in 2012 and 2023, alongside a slight decline in 2021, reflecting fluctuating scholarly attention. These results highlight the growing recognition of ethics as an essential element in educational strategies that advance sustainable development goals. The study emphasizes the importance of integrating ethical considerations into the development of inclusive, equitable, and sustainability-oriented educational objectives. The conclusions advocate for the establishment of ethically grounded educational frameworks that align with the objectives of Society 5.0, which aims to harmonize technological advancements with societal well-being. This research offers actionable insights for educators, policymakers, and researchers, providing strategies to strengthen the role of ethics in achieving educational and sustainable development objectives.